2008
DOI: 10.1177/1527154408318097
|View full text |Cite
|
Sign up to set email alerts
|

Personal Influencing Factors Associated With Pap Smear Testing and Cervical Cancer

Abstract: Pap smear is a screening test that detects abnormal cells before they advance to cancer. Unfortunately, not all women obtain routine screening. The method used was a qualitative study exploring personal influences regarding Pap smears. Face-to-face interviews with 7 low-income African American women who do and do not obtain Pap smears (between 21 and 37 years of age) were conducted at a health department about their social influence, previous health care experience, and cognitive appraisal regarding Pap smears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…Demographics and social support; inconvenient clinic hours, male providers, and insensitive staff; poor awareness of the indications and benefits of the cervical smear test; lack of knowledge of cervical cancer and its risk factors; fear of embarrassment, pain, or cancer; anxiety caused by receiving an abnormal cervical smear result, poor understanding of cervical screening procedures were among the factors influence a women's decision about cervical cancer screening (Fylan, 1998;Abercrombie, 2001;Ackerson et al, 2008;Cooper, 2011). Seow et al (1995) demonstrated that women's previous experience of Pap smears also influenced their intention to participate in screening programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Demographics and social support; inconvenient clinic hours, male providers, and insensitive staff; poor awareness of the indications and benefits of the cervical smear test; lack of knowledge of cervical cancer and its risk factors; fear of embarrassment, pain, or cancer; anxiety caused by receiving an abnormal cervical smear result, poor understanding of cervical screening procedures were among the factors influence a women's decision about cervical cancer screening (Fylan, 1998;Abercrombie, 2001;Ackerson et al, 2008;Cooper, 2011). Seow et al (1995) demonstrated that women's previous experience of Pap smears also influenced their intention to participate in screening programmes.…”
Section: Introductionmentioning
confidence: 99%
“…The findings are, however, intuitive, in line with prior expectations and show clear preferences for the attributes of interventions designed to overcome the well-documented reasons for non-attendance at screening. 4,[61][62][63][64] An 'opt-out' question with the choice 'not to screen' was not included as part of the experimental design in the DCE survey. Cervical screening is an area where women can choose not to be screened, as was the case with the target population in this study.…”
Section: Levels Of Opinionsmentioning
confidence: 99%
“…The objective of the IMCHB is to identify and suggest explanations for relationships between these three major elements. The IMCHB has previously been used because its ecological components are appropriate for health disparity studies where socio-environmental factors are an important consideration (Ackerson K et al, 2008). Ackerson et al (2008) used the IMCHB to guide the analysis of women's perceptions about cervical cancer screening (Ackerson K et al, 2008).…”
Section: The Evolution Of Behaviour Change Theoriesmentioning
confidence: 99%
“…The IMCHB has previously been used because its ecological components are appropriate for health disparity studies where socio-environmental factors are an important consideration (Ackerson K et al, 2008). Ackerson et al (2008) used the IMCHB to guide the analysis of women's perceptions about cervical cancer screening (Ackerson K et al, 2008). The BMHSU includes four components: a contextual level, an individual level, health behaviour, and health outcomes (Andersen R, 2008;Andersen RM, 1995;Phillips KA et al, 1998).…”
Section: The Evolution Of Behaviour Change Theoriesmentioning
confidence: 99%
See 1 more Smart Citation